PERKEMBANGAN ILMU PENGETAHUAN DAN LAHIRNYA MADRASAH SEBAGAI LEMBAGA PENDIDIKAN FORMAL - Muzakkir Muzakkir (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2010)
Science is essentially from Allah swt. He teaches and educates people through His selected person, His Messenger, with perfect teachings for all human beings in order that they can recognize himself and his God. The development of science is in line with the development of thinking and analytical skills of mankind. The trans-formation of knowledge to different people with different language is mainly by the process of translation. Trans-formation of knowledge, especially Islamic education began in a form of khalaqah in mosques or teachers' houses, then developed to be formal education known as madrasah.